Discovery of indazole aldosterone synthase (CYP11B2) inhibitors as potential treatments for hypertension. Issue 11 (1st June 2017) - Hoyt, Scott B.; Taylor, Jerry; London, Clare; Ali, Amjad; Ujjainwalla, Feroze; Tata, Jim; Struthers, Mary; Cully, Doris; Wisniewski, Tom; Ren, Ning; Bopp, Charlene; Sok, Andrea; et al.
Graphical abstract: Abstract: We report the discovery and hit-to-lead optimization of a structurally novel indazole series of CYP11B2 inhibitors. Benchmark compound34 from this series displays potent inhibition of CYP11B2, high selectivity versus related steroidal and hepatic CYP targets, and lead-like physical and pharmacokinetic properties. On the basis of these and other data, the indazole series was progressed to lead optimization for further refinement.